2017
DOI: 10.1371/journal.pone.0183387
|View full text |Cite
|
Sign up to set email alerts
|

History based forward and feedback mechanism in cooperative spectrum sensing including malicious users in cognitive radio network

Abstract: In cognitive radio communication, spectrum sensing plays a vital role in sensing the existence of the primary user (PU). The sensing performance is badly affected by fading and shadowing in case of single secondary user(SU). To overcome this issue, cooperative spectrum sensing (CSS) is proposed. Although the reliability of the system is improved with cooperation but existence of malicious user (MU) in the CSS deteriorates the performance. In this work, we consider the Kullback-Leibler (KL) divergence method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The outcome shows that these MUs in CSS increase the false alarm and misdetection, resulting in an increased interference to the primary transmission and reduced throughput of the network. Simulations confirmed that the proposed one-to-many relation based KLD method leads to more accurate and sophisticated detection than the traditional soft combination schemes in [46,47].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The outcome shows that these MUs in CSS increase the false alarm and misdetection, resulting in an increased interference to the primary transmission and reduced throughput of the network. Simulations confirmed that the proposed one-to-many relation based KLD method leads to more accurate and sophisticated detection than the traditional soft combination schemes in [46,47].…”
Section: Introductionmentioning
confidence: 65%
“…In this paper, Kullback Leibler Divergence (KLD) has been employed to protect the CSS against the spectrum falsification attack (SFA) of always no (AN), always yes (AY), random opposite (RO), and the always opposite (AO) categories of MUs by assigning weights to the sensing reports of SUs before global combination at the FC. In our previous study [46], SUs perform their local sensing, report soft energies to the FC, and also store this information in its local database. FC determines the KL divergence score against each user and also acknowledges this same information to the user.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, based on the flexible sensing time slot, τ p s using the KLD award score, each CR-IoT user to sense the PU licensed spectrum more efficiently. Now, we can calculate the KLD award score, δ of the proposed ED method using the flexible sensing time slot, τ p s with interference constraints for scenario II which is defined as between the two normally distributed functions f (ψ) and f (ψ) [5,50,51,59] as follows:…”
Section: Proposed Energy Detection Methods For Scenario IImentioning
confidence: 99%
“…In this paper, the CSS sensing performance is optimized in the presence of MUs reporting false information to the FC, by reducing miss detection and false alarm probabilities, resulting in overall reduction in error probability. In our previous study [30], SUs perform their local sensing and report soft energies to the FC and also store the information in their local database. After then, the FC determines the KL divergence score against each SU and also acknowledges this same information to the SU.…”
Section: Introductionmentioning
confidence: 99%